Evaluation of dental solid waste in Hamedan - Nabizadeh R.; Kulivand A.; Jonidi Jafari A.; Younesian M.; Omrani GH (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: Today, one of the most important environmental issues is dental solid wastes which are of great importance because of the presence of hazardous, toxic and pathogen agents. In this survey, solid waste produced in Hamedan general dental offices is evaluated. "nMaterials and Methods: In this descriptive study, from 104 general dental offices in Hamedan , 10 offices were selected in simple random way. From each offices, 3 sample at the end of successive working day (Sunday, Monday and Tuesday) were analyzed. Samples were manually sorted into different 74 components and measured by means of laboratory scale. Then, measured components were classified in the basis of characteristic and hazardous potential as well as material type. "nResults: Total annual waste produced in general dental offices in Hamadan is 14662.67 Kg (9315.45>95.0% Confidence Interval>20009.88). Production percentages of infectious, domestic type, chemical and pharmaceutical and toxic wastes were 51.93, 38.16, 9.47, 0.44 respectively. Main components of produced dental waste were 14 components that consist of more than 80 percents of total dental solid waste. So, waste reduction, separation and recycling plans in the offices must be concentrated on these main components. "nConclusion: In order to dental waste proper management, it is suggested that in addition to educate dentists for waste reduction, separation and recycling in the offices, each section of dental waste(toxic,chemical and pharmaceutical, infectious and domestic type wastes) separately and according to related criteria should be managed.